A Micro-level Study on the Use of Wood Asalternatnffi Source of Energy - Das, J. K.; Sarkar, A. (Indian Forester, 2005)
Farm forestry, a component of Social Forestry, is practised on a large scale and trees are planted on all available lands, including agricultural farms. A study was conducted in three districts of West Bengal to examine the social strata practising this component, to identify their reasons, to scrutinize the species being planted and wood-fuel supplementation effected by such plantations. The study was randomly designed and carried out and 165 farm foresters were included. The study shows that generally middle class strata, who are fairly educated and have only average land holdings, has taken up farm forestry. They plant trees for generating future income as a 'life insurance policy', followed by desire to meet fuelwood needs. They are aware of the gap between demand and supply of fuelwood and plan plantations keeping it in mind, but the species planted are not always suitable.